The history of science from the ancient Greeks to the scientific revolution - Spangenburg, Ray, 1939-; Moser, Diane, 1944- (Hyderabad : Universities Press, 1999)
Surveys the early history of science, discussing the philosophical underpinnings developed by Greek thinkers, continuing through the developments of the Middle Ages and the Renaissance, and concluding with the discoveries of the seventeenth century.
Includes bibliographical references and index.
Keywords: Science -- History -- Juvenile literature; Science -- History